Nutrition, weight control, and weight control risk knowledge, and dietary and weight regulation practice in elite gymnast of different levels of competition - Visiedo, A.; Frideres, J. E.; Palao, J. M. (European Journal of Human Movement, 2019)
The purpose of this study was to assess the level of nutrition, weight control, and weight control risk knowledge, and dietary and weight regulation practice of female gymnast of different levels of competition (regional, national, and international). The sample was 39 female rhythmic and aesthetic gymnastics athletes from the different levels of competition (15 gymnasts from regional level, 12 gymnasts from national level, and 12 gymnasts from international level). A self-administered questionnaire was used to measure the knowledge nutrition, weight control, and weight control risk knowledge and dietary practice. National and international gymnast had higher nutrition and weight control knowledge than regional gymnast. National and international gymnast skip more meals and have a significantly reduce intake of fruit, vegetables, and meat than regional gymnast. Gymnast of regional, national and international level do not have a proper perception about their knowledge and their risk of weight control on their bodies. This lack of adequate perception made recommended monitor the perception of these populations and provide them specific educational training.